Gravitation of large corporations in decentralized european cooperation with Chile (2000-2013); Gravitación de la gran empresa en la cooperación europea a pymes chilenas (2000-2013) - Pey-Grebe, C (Universidad Austral de Chile, 2025)
One of the main commitments undertaken by Chile in the 2000s was the Strategic Association Agreement with the European Union (2002), which included the cooperation pillar, with support for the internationalization of small and medium-sized enterprises (SMEs) as one of the central objectives of that section. However, its actual contribution to this sector was limited, both in terms of the amounts allocated and the lack of participation of these units. The article has as its general objective to describe how the strategies sought to influence audiences and “decision-makers,” granting powers to large European companies in key areas of the economy. It questions the real autonomy of development cooperation, being rather a case of “subordinated cooperation” as a form of soft power, in contrast to the commercial regimes and coercive mechanisms that have formed the basis of the European Union’s development offer since the early 1990s. © (2025), (Universidad Austral de Chile), All right reserved.